O mercado ilícito de ópio e a guerra estadunidense no Afeganistão (2001-2021) - Vieira, Maria Gabriela de Oliveira (2022)
This work aims to analyze the role of the illicit opium market in the evolution of the process of invasion in Afghanistan in 2001 by NATO forces. Despite being considered the largest illicit opium producer in the world since 1998, Afghan production has gained relevance on the international agenda in a context of the Global War on Terror following the September 11, 2001, attacks on the United States. More specifically when opium poppy production came to be considered a means of financing Taliban jihad. The US and UK, endorsed by UNODC, were primarily responsible for establishing such causality. From the contributions of the literature on the Political Economy of Conflicts applied to the US war in Afghanistan, it was possible to problematize this association and answer the research question, that is, how the prohibitionist orientation in relation to the opium production contributed to the deepening of the insecurity in the country? In addition to funding the actions of the belligerent actors, the undertaking of poppy eradication campaigns in a context of lack of alternative livelihoods distanced the population from the Afghan government engineered in Bonn and brought them closer to parallel power figures, be they insurgents or warlords. In this sense, the fact that opium is an important element in the dynamics of power in the country made it possible to understand that prohibitionism, crystallized in eradication campaigns and in interdiction operations, contributed to accelerating the resumption of the historic process of empowerment of the rural periphery in relation to the urban center in Afghanistan